Tegumentary system of the vicuña (V. vicuña) SEPARAR RESALTAR (Veterinary Science, 2017)
Samples of different cutaneous areas of mature vicuñas (V. vicugna) were studied microscopically. Thickness of skin, annexed glands and pileous follicles were considered. Follicular groups were of variable siza according to area and contained a greater quantity of follicles in back skin than the flanks. There were also main and secondary follicles within the follicular groups
Keywords: Camelids; Vicuña; Skin